2017
DOI: 10.22616/erdev2017.16.n142
|View full text |Cite
|
Sign up to set email alerts
|

Heat-mass transfer in layer of berries during freezing process

Abstract: Abstract. Qualitative changes of berries during freezing have been investigated with instrumental methods. In order to economize energy it is proposed to determine the freezing temperature of products. The objective characterisation of physical properties of products enabled to evaluate the quality, to incorporate it into the technological regimes of the treatment. Numerical results of process modelling are shown. The freezing regime is defined by several thermo-physical parameters of the production. Water sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Based on [37] work, a numerical method applicated to a coupled heat mass transfer model for freezing berry layers and showed that freezing temperature plays a role in predicting freezing time. Parameter such temperature highly depends on time and position [38].…”
Section: Heat and Mass Transfer Modelmentioning
confidence: 99%
“…Based on [37] work, a numerical method applicated to a coupled heat mass transfer model for freezing berry layers and showed that freezing temperature plays a role in predicting freezing time. Parameter such temperature highly depends on time and position [38].…”
Section: Heat and Mass Transfer Modelmentioning
confidence: 99%
“…In addition, when a food is frozen, part of the water is transformed into ice, thus decreasing the food’s water activity [ 8 ]. This decrease influences the growth of many microorganisms, since they cannot develop in low water activity conditions [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%